Digital media processing for multimedia interactive services : (World Scientific, 2003)
This volume contains papers describing state-of-the-art technology for advanced multimedia systems. It presents applications in broadcasting, copyright protection of multimedia content, image indexing and retrieval, and other topics related to computer vision.